1996
DOI: 10.1046/j.1365-2141.1996.d01-1906.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell phenotypes in the α+ thalassaemias from early childhood to maturity

Abstract: The alpha+ thalassaemias are the most common single gene disorders of humans, yet little is known about their haematological characteristics in childhood. Blood samples have been collected randomly from more than 2000 individuals in village communities in Vanuatu in the South West Pacific and analysed for alpha thalassaemia and associated haematological changes. Here we describe the haematological effects of the alpha+ thalassaemias from early childhood through to maturity in this population. Mean cell volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 12 publications
5
33
3
Order By: Relevance
“…This is in accordance with an earlier study reported that the -α 3.7 deletion at the heterozygous state has no effect, except on MCH values and this occurs only in childhood (Williams et al 1996).…”
Section: α-Thalassaemia In Tunisiasupporting
confidence: 94%
“…This is in accordance with an earlier study reported that the -α 3.7 deletion at the heterozygous state has no effect, except on MCH values and this occurs only in childhood (Williams et al 1996).…”
Section: α-Thalassaemia In Tunisiasupporting
confidence: 94%
“…Although admission hemoglobin concentrations were similar between genotypic groups (Table 3), the trend toward increasing hemoglobin values across the groups is noteworthy, given that heterozygous and homozygous ␣ ϩ thalassemia are associated with anemia at steady state. 11 We found no effect of ␣ ϩ thalassemia on admission parasite density.…”
Section: Resultsmentioning
confidence: 50%
“…Routine tests can be unreliable; for example, microcytosis is a poor indicator in populations where hemoglobinopathies are common 1,2 and acute malaria can result in both anemia 3 and elevated serum ferritin concentrations. 4,5 The transmembrane iron transport protein transferrin receptor (CD71) is a dimeric protein consisting of two identical 95-kD subunits.…”
mentioning
confidence: 99%